Advances in E3 ubiquitin ligase BRUTUS and its homologous proteins regulating plant responses to biotic and abiotic stresses - JING Xiangting; JIN Chongwei (浙江大学学报. 农业与生命科学版)
The ubiquitination pathway of proteins plays an important role in plant responses to biotic and abiotic stresses. In recent years, the E3 ubiquitin ligase BRUTUS (BTS) has gradually attracted extensive attention from scientists worldwide because of its involvement in the regulation of plant growth and development and responses to a variety of stresses. In this paper, the structural characteristics of BTS and its homologous proteins in plants were described in detail, and the mechanisms of BTS in response to biotic and abiotic stresses such as mineral nutrient stress, heavy metal pollution stress, drought stress, high light intensity stress, and pathogen stress were reviewed. At the same time, this paper summarized several problems in current related studies, and it looks forward to other potential functions of BTS and future research directions.